Would You Want to Buy an Expensive Handbag without a Logo? – The Role of Conspicuous in Luxury Handbag Consumption in China - Chen, Hanpu; Walsh, John (Journal of Ecohumanism, 2024)
Luxury handbags give customers more spiritual value with the idea of expensive, but not cost-effective, high-brand premium products. Many studies have pointed out that purchasing handbags tends to give consumers the perception of higher social class and successful status. Besides, other studies pointed out that people have spiritual satisfaction because luxury handbags are expensive, as well as the recognition of the senior class of society. However, some studies point out that people buy luxury goods because they identify with the brand and feel that the successful brand fits their identity. Therefore, this study needs to explore the motivation for purchasing luxury handbags and the stimulators of the motivations. From the perspective of the purchasing trend of luxury handbags, the consumption power of China is on the rise. Therefore, this study takes Chinese consumers as the research object and interviews 15 customers from Shanghai, Hangzhou, Ningbo, Chengdu, Qingdao, and Zhengzhou who have the purchasing experience of luxury handbags via qualitative research method. It takes quantitative research for 371 respondents to explore the relationship between brand users’ image, brand self-congruity, conspicuous, and purchase intention. This study found that brand uses’ image, self-congruity, and conspicuous a on purchase intention. Then, brand self-congruity mediates the relationship between brand users’ image and purchase intention. The conspicuous acts mediate between brand users’ image and purchase intention, brand self-congruity, and purchase intention, respectively. The results of this study can support merchants in building and promoting their brands better via customer psychology and can provide ideas for marketing activities for luxury brands based on the motivation formed by potential customers.